Pengaruh Motivasi Kerja, Kepemimpinan dan Lingkungan Kerja Terhadap Disiplin Kerja Aparatur Sipil Negara pada Dinas Perhubungan Kota Surakarta - Fitri Novia Kusuma; Asih Handayani (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to analyze the significance of the influence of work motivation, leadership and work environment on work discipline. The type of data used is quantitative. The data source used is quantitative. The primary data source used is primary data. The sampling technique used was a saturated sample with a total of 63. Data collection techniques in this research used observation, questionnaires and literature study. The instrument test in this study used a validity test and a reliability test. The classical assumption test uses the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test. Data analysis techniques use multiple linear regression tests, t tests, F tests and R2. The results of the validity and reliability tests show that all statements regarding work motivation, leadership, work environment and work discipline are declared valid because the p value is < 0.05 and reliable because Cronbach's alpha is > 0.60. The results of the classical assumption test show that all variables have passed the multicollinearity test, autocorrelation test, heteroscedasticity test and are normally distributed. The results of the regression analysis obtained the equation Y = -2.831+ 0.114 X1 + 0.641 X2 + 0.307 X3 + e. The results of the t test showed that work motivation (X1) had no significant effect on work discipline, while leadership (X2) and work environment (X3) had a significant effect on work discipline. The results of the F test showed that the regression model used in this research was correct. The R2 test results show that the contribution of the independent variable to the dependent variable is 59.7%, the remaining 40.3% is explained.